Characterization of group B Streptococcus colonization in full-term and Late-Preterm neonates in Taiwan - Jen-Fu Hsu; Chyi-Liang Chen; Chien-Chung Lee; Reyin Lien; Shih-Ming Chu; Ren-Huei Fu; Ming-Chou Chiang; Chang-Yo Yang; Mei-Yin Lai; I-Hsyuan Wu; Yu-Shan Yen; Cheng-Hsun Chiu (Pediatrics and Neonatology)
Background: Group B streptococcus (GBS) infections can be life-threatening in newborns. This study aimed to analyze GBS carriage status and genotypic diversity in healthy neonates after implementation of intrapartum antibiotic prophylaxis (IAP) in Taiwan. Methods: Newborns carrying GBS were identified from a screen of 500 newborns and followed up until their cultures turned negative. Their mothers' GBS screening data were reviewed. Molecular methods, including capsular serotyping, multilocus sequence typing and pulsed-field gel electrophoresis (PFGE), were used to analyze GBS isolates. Results: GBS colonization was detected at either the nose or anus in 11 of 500 healthy neonates (2.2%). In this group of 11 neonates, 4 had GBS serotypes II and III for 4–6 months, 1 had serotype V for 2 months, 6 had serotypes Ia, II, V, and VI for less than 1 month, and 1 had 2 different serotypes (serotypes V and II) at different times. The most prevalent serotype was II (33.3%), followed by Ia (25.0%), III (16.7%), V (16.7%), and VI (8.3%). The main sequence type was ST1 (50.0%), followed by ST19 (16.7%), ST23 (8.3%), ST24 (8.3%), ST103 (8.3%), and ST 231 (8.3%). All isolates were grouped into 5 PFGE clusters F, G, J, X, and Y, and all were susceptible to β–lactam antimicrobial agents. Conclusions: GBS was carried in 2.2% (11/500) healthy newborns and persisted for 6 months in 3 neonates. This study makes clearer our understanding of GBS colonization, serotype distribution, and genotype distribution in healthy neonates. Key Words: colonization, group B Streptococcus, intrapartum antibiotic prophylaxis, PFGE, sequence type